EFEKTIVITAS EKSTRAK ETANOL DAUN TEH CAMELLIA SINENSIS 50% SEBAGAI ANTISEPTIK TANGAN - Monica Oktaviana; Johannes C Prihadi; Lucky H. Moehario (Bahasa Indonesia, 2021)
Introduction: : Practicing hand hygiene is a way to control an infection. The recent COVID-19 pandemic, hand hygiene has become the necessity. Using antiseptic which contain chemical active ingredients causes skin problem. Camellia sinensis is a natural ingredient which its antimicrobial properties is due to the presence of catechin. The study was aimed to determine the effectivity of ethanol extract of Camellia sinensis tea leaves as hand antiseptic. Methods: This research was a comparative experimental analytic to 32 respondents conducted in the Microbiology Laboraroty of Faculty Medicine and Health Sciences–Atma Jaya Jakarta Catholic University of Indonesia. Sampling was carried out by taking bacterial swabs on the right palms. Followed by dilution using serial dilution method and inoculated onto nutrient agar using the spread plate technic. After incubation at 37oC overnight the bacterial colonies were calculated using colony counter within a range of 30-300 colonies per plate. Wilcoxon and Mann-Whitney was used for data analysis. Results: The total number of bacterial colonies after sanitizing using 50% ethanol extract of Camellia sinensis tea leaves was reduced by 55.04% (p=0.003). Meanwhile, 70% alcohol curb the bacterial colonies by 76.84% (p=0.000). The comparison of the effectivity of 50% ethanol extract of Camellia sinensistea leaves versus 70% alcohol as hand antiseptic was insignificance (p=0.300). Conclusion: 50% ethanol extract of Camellia sinensis tea leaves showed activity against hand’s microorganisms. However, the percentages of Camellia sinensis extract might be increased so as to achieve the effectivity of 70% alcohol.